Correction: Shaikh et al. Acoustic Propagation and Transmission Loss Analysis in Shallow Water of Northern Arabian Sea. J. Mar. Sci. Eng. 2024, 12, 2256 - Shahabuddin Shaikh; Yiwang Huang; Ayman Alharbi; Muhammad Bilal; Abdul Sami Shaikh; Habib Hussain Zuberi; Muhammad Ayoob Dars (Journal of Marine Science and Engineering)
Errors in Figures [...]